Prioritization of road projects — A disutility based approach - Maitra, Bhargab; Azmi, Moen; Ibrahim, S. N. (Transport, 2002)
In order to boost the economic growth India has initiated a massive road infrastructure development programme. However, due to serious constrains in financial resources, non-availability of adequate technical manpower, institutional constraints etc., it is not possible to execute all the necessary road development projects within a short time span. Besides, it is essential to prioritize roads on a logical rational basis and target the development in a phased manner. In the present paper the a methodology has been proposed for the prioritization of road development. Relevant influencing factors for prioritization have been identified and their relative weights have been estimated based on an expert-opinion survey. The total disutilities on existing roads have been measured and the prioritization has been proposed on the basis of estimated total disutility. The methodology demonstrated in the paper is simple and requires data which are either available from secondary sources or may be obtained easily from simple primary surveys.First Published Online: 19 Oct 2011